Diffuse gliomas: insights into clinical and histopathological features and survival rates from two centers in a middle-income country - Ordóñez-Rubiano, Edgar G.; Siabato, Cristian; Rincón-Arias, Nicolás; Pulido, Paula A.; Pimienta-Redondo, Hebert D.; Espinosa-Gaona, Sebastián; Useche-Diosa, Santiago; Moreno, María Andrea; Cifuentes-Lobelo, Hernando A.; Zorro-Guio, Oscar F.; Patiño-Gómez, Javier G.; Cómbita, Alba Lucía; et al. (Frontiers in Oncology, 2025)
IntroductionGliomas are believed to arise from neuroglial stem cells and are histologically classified based on morphological similarities to normal neuroglial cells. This study aims to describe the clinical, histopathological, and demographic features of glioma patients treated in two reference centers in Colombia.MethodsThis descriptive cross-sectional study included all patients with a histologically confirmed glioma treated at two institutions in Bogotá, Colombia, between January 2015 and December 2023. 272 patients with diffuse gliomas were included, and data were collected on sociodemographic characteristics, clinical presentation, histopathologic diagnosis, immunohistochemical markers, extent of resection, functionality, complications, and survival.ResultsAmongst all cases, 36.00% were glioblastomas, 14.70% oligodendrogliomas, and 12.10% astrocytomas. 49.10% of patients were females, average age was 48.8 ± 21.0 years. While in the frontal lobe, most glioblastomas (38.95%) and oligodendrogliomas (47.50%) were found, astrocytomas were more frequent in the insula (27.27%). The average follow-up was 11.8 ± 16.0 months. Near-total resection was achieved in 40.10% of patients, followed by subtotal resection (37.00%), gross-total resection (11.45%), and intentional biopsy (11.45%). 31.25% of patients had new-onset motor deficits, and only 3% persisted after the 3-month follow-up. Overall survival was higher in females (males: 28.57% vs. females: 55.00%) (p = 0.0013). The 2-year overall survival for glioblastoma was 21%, 5-year for glioma, NOS 38%, for astrocytoma 15%, and 8-year for oligodendroglioma 5% (p < 0.0001).ConclusionsWe present the largest study to date of diffuse glioma in Colombia’s population. Clinical findings and overall survival trends are similar to those reported worldwide, however, further molecular analysis is needed for adequate diagnosis and classification